Comparative Analysis of Diffraction Grating on a Hair and a Broom as an Alternative Experiment in School - Asa Manafia Mumtaza; Farah Fairuz Khairun Nisa; Ahmad Suryadi; Siti Humairoh; Fuji Hernawati Kusumah (Jurnal Multidisiplin Indonesia, 2023)
Laboratory experiments in schools often face challenges, including inadequate teacher training, limited equipment and materials, and dense teaching content. This research proposes an alternative approach by using readily available materials in the school environment. In the diffraction experiment, banana leaf stems were replaced by coconut fiber and a strand of hair as experimental media. Fraunhofer diffraction, the bending of waves behind a narrow slit, became the focus of this experiment. The primary objectives were to understand the process of diffraction grating, measure the differences in spreading between a strand of hair and coconut fiber, and analyze the variables involved. The experimental data showed that a strand of hair had the farthest distance to the central bright spot with an average of 1.23 meters. While successfully creating a diffraction grating pattern using makeshift tools and materials, the difficulty in measuring the distance between bright spots highlighted a critical note for future improvements. In conclusion, this experiment provides new insights into light diffraction using resources available in the school environment. However, further research expansion and improved measurement accuracy should be the focus to support the development of more effective laboratory methods in overcoming facility limitations in the school environment.